Classification of urban soils, differentiation of their antropogenic diagnostic properties on the example of soils in Szeged - Puskás, Irén; Farsang, Andrea (JOURNAL OF LANDSCAPE ECOLOGY, 2007)
Urban soils have greatly different characteristics than natural ones. This is caused by their main influencing and altering factor, the anthropogenic interference. We collected the soil samples from the horizons of 15 profiles in Szeged during the spring of 2005. Besides sampling soil profiles, topsoil samples (0–10 cm depth, 2–4m2) were also taken. Heavy metal concentration (Co, Cu, Ni, Pb, Zn, Cr) was determined from these samples. The aims of this study were the examination of diagnostic properties (coarse material, heavy metal content, organic matter content, qualitity of organic matter, pH (H2O, KCl), carbonate content, nitrogene content) different from natural soils and the categorization of the profiles according to an existing urban soil classification system.
Keywords: Szeged; urban soils; soil classification; heavy metals